Localized- and advanced-stage follicular lymphomas differ in their gene expression profiles - Staiger, Annette M.; Hoster, Eva; Jurinovic, Vindi; Winter, Stefan; Leich, Ellen; Kalla, Claudia; Möller, Peter; Bernd, Heinz-Wolfram; Feller, Alfred C.; Koch, Karoline; Klapper, Wolfram; Stein, Harald; et al. (Blood, 2020)
About 20% of follicular lymphomas present as localized-stage disease. Intriguingly, only half carry t(14;18). Staiger and colleagues have identified distinct ge